(untitled) (Konferensiyalar | Conferences, 2024)
This article focuses on a comparative analysis of music terms in English and Uzbek languages, highlighting the differences and similarities in vocabulary, semantic associations, and cultural influences. English has a diverse music vocabulary influenced by various cultures, while Uzbek music terms reflect the unique cultural values and traditions of the region. The article provides examples of music terms associated with specific musical traditions in Uzbekistan, such as shashmaqam, maqom, and surnay. It also presents examples of music terms associated with musical traditions in English-speaking countries, including Baroque music, blues, jazz, and musical theater. Translating music terms between the two languages presents challenges due to cultural context and linguistic differences. The analysis of music terms has pedagogical implications for language learners and can enhance linguistic skills, cultural awareness, and musical knowledge. Overall, the comparative analysis sheds light on the interplay between language, culture, and music.